2022
DOI: 10.1371/journal.pone.0270311
|View full text |Cite
|
Sign up to set email alerts
|

Positivity rates of SAR-CoV-2 infection in orthodontic patients at the orthodontic clinic, University of Illinois Chicago

Abstract: COVID-19 has impacted and increased risks for healthcare providers, including orthodontists. There is no information regarding the potential transmission risks in the orthodontic community. This study aims to compare the positivity rate of SARS-CoV-2 infection in orthodontic patients at the University of Illinois Chicago (UIC) orthodontic clinic to the positivity rate of the local population in Chicago. All orthodontic patients who sought treatment at the UIC orthodontic clinic from June 16 to October 31, 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, the validated and comprehensive set of questionnaire in this study provides information of practice management and evidence for the orthodontic practices for the preparation of orthodontic practice for the future pandemic event. A recent report showed the positivity rate in orthodontic patients was 0.626% and a potential risk of COVID-19 transmission from patients to orthodontic providers remains, even with asymptomatic and vaccinated patients [ 15 ]. Our survey respondents cited the ADA website (80.9%), CDC website (74.2%), and state dental association websites (58.1%) as the most commonly used sources for COVID-19 information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validated and comprehensive set of questionnaire in this study provides information of practice management and evidence for the orthodontic practices for the preparation of orthodontic practice for the future pandemic event. A recent report showed the positivity rate in orthodontic patients was 0.626% and a potential risk of COVID-19 transmission from patients to orthodontic providers remains, even with asymptomatic and vaccinated patients [ 15 ]. Our survey respondents cited the ADA website (80.9%), CDC website (74.2%), and state dental association websites (58.1%) as the most commonly used sources for COVID-19 information.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 also affected the mental health of dental healthcare workers as fluctuated anxiety and depression [ 13 , 14 ]. Few studies reported the positivity rates of patients seeking dental treatments including emergency, pediatric and orthodontic treatments ranging from 0.027 to 6.7% [ 15 19 ]. Due to its high transmitted nature, COVID-19 leads to the report of 99.7% of dentists enhancing PPE protocols to mitigate the COVID-19 transmission [ 11 ].…”
Section: Introductionmentioning
confidence: 99%